Association between air pollutants, thyroid disorders, and thyroid hormone levels: a scoping review of epidemiological evidence - Yang, Kaijie; Zhang, Guofeng; Li, Yongze (Frontiers in Endocrinology, 2024)
Background Over the past two decades, the incidence of thyroid disorders has been steadily increasing. There is evidence to suggest that air pollution may be one of the etiological factors of thyroid diseases. This comprehensive review aimed to examine the evidence related to air pollutants and thyroid disorders and thyroid hormones levels from an epidemiological perspective. Methods The scoping review adopted a systematic approach to search for, identify, and include peer-reviewed articles published in English. We performed a comprehensive search of three databases-PubMed, Embase, and Web of Science to identify relevant literature on the relationship between air pollution [particulate matter, nitrogen oxide, carbon monoxide (CO), ozone (O3), sulfur dioxide (SO2)] exposure and thyroid disorders, including hypothyroidism, congenital hypothyroidism (CH), thyroid nodules, thyroid cancer, autoimmune thyroid diseases, as well as thyroid hormone levels, such as thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4). Articles published until August 1, 2023, were included. Results A total of 3,373 studies were retrieved, and among them, 25 studies covering eight different air pollutants were relevant. The most frequently studied air pollutants in this review included fine particulate matter (with fine particulate matter (PM2.5), n=21; inhalable particles (PM10), n=10; PM10-2.5, n=1) and nitrogen oxides (with NO2, n=13; NOx, n=3). The thyroid disorders and thyroid hormone levels most commonly associated with evidence of air pollution exposure were hypothyroidism (n=7) and TSH (n=12). Conclusions Despite variations in study designs and exposure assessments, the findings consistently highlight the substantial health risks that air pollution, particularly PM2.5, poses to thyroid health, especially among vulnerable populations. Given that our study was limited to epidemiological investigations and the increasing prevalence of toxic substances in the environment, there is an urgent need for further research to elucidate the mechanisms by which these pollutants disrupt thyroid function and contribute to the development of thyroid diseases.